Welcome - Jeffers, Joshua (The Toro Historical Review, 2023)
Welcome to volume 14, issue 2 of The Toro Historical Review! Congratulations to the authors: Sylvia Duvenary, Daniella J. Enriquez, Christopher Garcia, Lauren Heib, Anthony Rojo, Francisco Sanchez, and Nicholas Velastegui. And a special thank you to our editorial team who has worked hard to bring this issue to fruition. Thank you! This issue features seven essays produced in upper-division history classes and represents remarkable achievements in undergraduate research, writing, and editing. Well done all!